The Ruptured Aneurysm Patient's Disability Correlation with Autoregulatory Measures, Spreading Depolarization, and Vasospasm. (16th November 2020) - Fritch, Chanju; Owen, Bryce; Shuttleworth, C. William; Carlson, Andrew P
Abstract: INTRODUCTION: Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating disease associated with disability following patient's hospital course. Traditionally, vasospasm has been held responsible for the worsening of a patient's in-hospital clinical status and expected eventual post-hospital outcome, however, heterogeneity within previous studies has shown this paradigm to be incomplete. Within the aSAH population, impaired cerebral autoregulation has also been shown to correlate with unfavorable outcome, and spreading depolarization (SD) has been shown to be a mechanism of spreading ischemia and resultant decline in some of these patients. METHODS: his prospective observational study enrolled patients undergoing craniotomy and clipping for aSAH. Subdural electrocorticographic (ECoG) strips were placed at the completion of surgery to detect spreading depolarizations. Additionally, a multi-modal probe was placed during the post-operative course, allowing for examination of cerebral blood flow (CBF), intracranial pressure (ICP), and tissue oxygenation (PbtO2). Vasospasm was recorded as none, mild, moderate, or severe. The Pearson correlation coefficient between ICP/PbtO2/CBF and MAP (Prx, Orx, and CBFx, respectively) were calculated in standard fashion. Outcome was measured with a 3-month modified Rankin scale (mRS) and dichotomized into good (mRS 0–3) and poor outcomes (mRS 4–6). Logistic regression was calculated between reactivity (Prx, Orx, CBFx) and outcome. A similar logistic regression was calculated for rate of SDs and vasospasm was evaluated using Chi-squared. RESULTS: 32 total patients were enrolled, with 30 (94%) receiving ECoG monitoring and 22(68%) receiving multi-modal CA monitoring. Of the 30 patients with ECoG, 26 had at least 1 SD, and the average number of SDs was 11.5. Of the 32 patients, 7 expired over the course of their hospitalization, and post-hospital outcomes were favorable (mRS 0–3) in 15. The rate of SD and vasospasm were not correlated with outcomes ( P = . 71 and P = . 91, respectively). ORx and Prx were the only CA measures that demonstrated a statistically significant correlation with functional outcome ( P = . 003 and P = .0008, respectively). CONCLUSION: These data reaffirm the utility of cerebral autoregulation as a valuable measure to evaluate patient status and outcome prognostication following aneurysm treatment.